Urgensi Fast Track Legislation Dalam Pembentukan Undang-Undang Di Indonesia - lestari, Fika; Haryono, Dodi; HB, Gusliana (Peneliti.net, 2024)
Fast Track Legislation is the process of forming laws through discussion stages that can be carried out quickly to avoid the process of forming legislative regulations being very fast, giving the impression of being haphazard. With the presence of the concept of fast track legislation, it at least limits and gives authority to anything that can be said to be a fast legislative process. The presence of fast track legislation in Indonesia not only creates regularity in structuring legislative functions in responding to emergency or urgent events but also places limits on a legislative process that can be carried out quickly. This research aims to find out the arrangements and practices of Fast Track Legislation in Indonesia, to find out the arrangements and practices of Fast Track Legislation in various countries and to find out projections for the adoption of Fast Track Legislation into the law formation system in Indonesia. The regulation and practice of Fast Track Legislation in various other countries, namely New Zealand, is based on motion urgency. The United Kingdom recognizes the existence of a fast track legislation mechanism to meet people's needs quickly. The United States regulates fast-track legislation in the House Rules and Manual and Ecuador, as stated in Article 140 of the Ecuador Constitution, regulates fast-track legislation. Regulations and practices of Fast Track Legislation in Indonesia where positive law in Indonesia does not specifically regulate fast track legislation mechanisms. The projected adoption of Fast Track Legislation into the law formation system in Indonesia cannot be separated from 2 (two) criticisms if it is later adopted in the formation of laws in Indonesia, namely, first, concerns about the loss of public participation in discussing laws.